Experimental study on cyclic shear stiffness and damping ratio of carbonate sand-steel interface - RUI Sheng-jie; GUO Zhen; WANG Li-zhong; ZHOU Wen-jie; LI Yu-jie (Rock and Soil Mechanics, 2020)
The dynamic response of carbonate sand-steel interface is of great significance to the safety and stability of the structure foundations which are constructed under reef geotechnical conditions. To investigate the effects of normal stress, cyclic amplitude and particle size on the interface shear stiffness and damping ratio, a series of cyclic shear tests on the interface between carbonate sand and steel was carried out based on the interface ring shear apparatus, and further compare these properties of carbonate sand with quartz sand. The results indicate that normal stress and cyclic amplitude have significant effects on the interface shear stiffness and damping ratio. Specifically, the promotion of normal stress level increases the shear stiffness and meanwhile decreases the damping ratio; the enhancement of cyclic amplitude leads to an approximate inverse reduction of shear stiffness and an approximate logarithmic increase of damping ratio; for carbonate sand with a uniform particle size, there is a critical particle size which results in a significantly different interface shear behavior. When the particle size of quartz sands is large, the shear stiffness and damping ratio are significantly different from those of carbonate sands. However, if the particle size is small, the shear stiffness and damping ratio of these two sands are almost consistent with each other.